The clinical spectrum associated with ERCC5 mutations: Is there a relationship between phenotype and genotype? - Jinpeng Zhang; Jiannan Ma; Yuanyuan Luo; Siqi Hong; Li Jiang; Tianyi Li (Pediatric Discovery)
Abstract Mutations in the ERCC5 gene can lead to different clinical phenotypes, few articles have reported the clinical phenotypes in detail and explained the relationship between genotype and phenotype. The clinical data of cases with ERCC5 gene mutations diagnosed in our center and reported in previous studies were collected. The cases were divided into three groups based on phenotype; the differences of clinical manifestation and genotype among groups were analyzed. Genetic tests showed a complex heterozygous mutation of the ERCC5 gene with paternal C.402_C.403 (exon 4) insA (p.T135Nfs*28) and maternal C.1096 (exon 8) C > T (p.R366X.821) in our case. The gene mutation has not been reported and was predicted to seriously affect the protein structure. According to a review of 59 cases of ERCC5 mutations, cerebrooculofacioskeletal syndrome (COFS) occurred in 16 cases, XP in 19 cases, and XP/CS in 24 cases. The incidence of physical retardation, mental retardation, peripheral neuropathy, magnetic resonance abnormalities and fundus/vision abnormalities in XP/CS patients was significantly higher than that in XP patients. In addition, patients with the XP/CS phenotype were more prone to appearance abnormalities, deafness, and epilepsy, and cheilitis and tumors were more common in patients with the XP phenotype, but the differences were not significant. XP/CS can cause abnormal liver function and even fatality, which should be given attention. ERCC5 mutation‐related diseases were characterized by mild to severe clinical phenotypes. In addition to tumors, liver function should be considered in ERCC5‐related diseases, and patients should be cautious with medication to avoid drug‐induced liver injury.